Kemiskinan Pada Gelandangan Dan Pengemis (Gepeng) Diperkotaan: Perspektif Teori Habitus Oleh Pierre Bourdieu - Octy Astrid Nasution; Yohanes Bahari (Departement of Mathematics Education, 2024)
The poverty that is scattered in Indonesia's big cities is a complex and worrying social problem. This article uses the habitus theory approach by Pierre Bourdieu to understand the causes and socio-economic implications of this phenomenon. Habitus theory explains how individuals form their patterns of thinking, attitudes and behavior through social and environmental interactions. Poverty and socio-economic inequality are the main factors that influence the formation of individual habits that drive them to become beggars. The social and economic implications of sprawl include social inequality, impacts on health and welfare, and disruption to community safety and comfort. By understanding the relationship between habitus and the phenomenon of sprawl, this article suggests a holistic approach in overcoming it, including efforts to improve access to basic services, economic empowerment, community awareness campaigns, and collaboration between government, non-governmental organizations and the community. Further research is needed to develop more effective strategies to overcome sprawl and improve community welfare in large cities